2019
DOI: 10.1029/2018gl079944
|View full text |Cite
|
Sign up to set email alerts
|

High Temporal Resolution Monitoring of Small Variations in Crustal Strain by Dense Seismic Arrays

Abstract: We demonstrate the feasibility of detecting very weak deformation in the shallow crust with high temporal resolution by monitoring the relative changes in seismic wave velocity (dv/v) using dense arrays of seismometers. We show that the dv/v variations are consistent between independent measurements from two seismic arrays. Dominant peaks in the observed dv/v spectrum suggest that tides and temperature changes are the major causes of daily and subdaily velocity changes, in accordance with theoretical strain mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 53 publications
5
78
1
Order By: Relevance
“…The traveltime changes are divided by the absolute traveltimes d t / t (Figure ), inverse to the relative velocity changes d v / v , are of the order 10 −4 (Figure 9a). These amplitudes of d v / v are of an order similar to the previous observations from active (e.g., Reasenberg & Aki , ) and passive source monitoring (e.g., Mao et al, ).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…The traveltime changes are divided by the absolute traveltimes d t / t (Figure ), inverse to the relative velocity changes d v / v , are of the order 10 −4 (Figure 9a). These amplitudes of d v / v are of an order similar to the previous observations from active (e.g., Reasenberg & Aki , ) and passive source monitoring (e.g., Mao et al, ).…”
Section: Resultssupporting
confidence: 87%
“…However, our velocity change correlate well to the tide in 1-day period (cc = −0.90; Figure 11b) but poorly correlates to the stronger half-day (cc=−0.21; Figure 11c) and broadband (cc = −0.49; Figure 11a) tides. Furthermore, Earth tides are believed to cause instant velocity changes (Mao et al, 2019;Reasenberg & Aki, 1974), which are not observed here. Therefore, the solid Earth tide is unlike the primary cause of the observed velocity changes.…”
Section: Solid Earth Tidementioning
confidence: 64%
See 2 more Smart Citations
“…This can provide insights not only into the tectonic and volcanic processes (Brenguier, Campillo, et al, ; Brenguier, Shapiro, et al, ; Brenguier et al, ; Chen et al, ; Froment et al, ; Obermann et al, ; Taira & Brenguier, ; Wegler et al, ) but also into some transient fluctuations that are derived from external environmental perturbations (Sens‐Schönfelder & Wegler, ; Meier et al, ; Hillers et al, ; Hillers, Ben‐Zion, et al, ; Wang et al, ). The characteristic depth at which such changes can be monitored varies from meters (Hillers, Retailleau, et al, ; Mao et al, ; Sens‐Schönfelder & Wegler, ) down to dozens of kilometers into the crust (Froment et al, ; Obermann et al, ; Rivet et al, ), through measurements at various periods. Our goal here is to investigate changes down to 40 km in depth at a regional scale after a significant earthquake.…”
Section: Introductionmentioning
confidence: 99%